MQAPsingle: A quasi single‐model approach for estimation of the quality of individual protein structure models. Issue 8 (24th May 2016) - Pawlowski, Marcin; Kozlowski, Lukasz; Kloczkowski, Andrzej
ABSTRACT: We present a Model Quality Assessment Program (MQAP), called MQAPsingle, for ranking and assessing the absolute global quality of single protein models. MQAPsingle is quasi single‐model MQAP, a method that combines advantages of both "pure" single‐model MQAPs and clustering MQAPs. This approach results in higher accuracy compared to the state‐of‐the‐art single‐model MQAPs. Notably, the prediction for a given model is the same regardless if this model is submitted to our server alone or together with other models. Proteins 2016; 84:1021–1028. © 2015 Wiley Periodicals, Inc.